Financial Technology dan Kredit Bank Umum Konvensional di Indonesia - Sahdan Saputra; Stevany Hanalyna Dethan; Baiq Rabiatu Adawiyah Kartika Wulan; Ridha Nurul Hayati (Universitas Bumigora, 2022)
This study analyzes the impact of FinTech on the number of conventional commercial bank loans in Indonesia. This study used a sample of 40 conventional commercial banks in Indonesia listed on the Indonesia Stock Exchange for the 2016-2021 period. The number of observations in the study was 240. FinTech is measured using P2P Lending and FinTech companies are measured using the growth period of FinTech companies. The results of the research based on the regression test using the Fixed effects model, this study proves that P2P lending and the growth of FinTech companies have a positive and significant effect on the amount of lending to Conventional Commercial Banks in Indonesia. This means that the greater the P2P lending disbursed by FinTech companies and the higher the growth of FinTech companies, it will have an impact on increasing the number of conventional commercial bank loans in Indonesia. One of the important variables not examined in this study is payments made online. Therefore, further research can expand research with the same theme by presenting online payment variables.